Base pairing and mutagenesis: observation of a protonated base pair between 2-aminopurine and cytosine in an oligonucleotide by proton NMR. - Sowers, L C (1986)
2-Aminopurine (AP), a potent mutagenic base analogue, most frequently pairs with thymine. In the AP X T base pair, both bases adopt normal tautomeric forms. The mechanism for the mutagenic activity arises from its observed pairing with cytosine, which has been ascribed to an enhanced tendency to adopt the rare imino tautomeric form. NMR studies in H2O on all the exchangeable protons in an oligonucleotide duplex containing an AP X T base pair show Watson-Crick hydrogen bonding. When the thymine is replaced by cytosine in the duplex, we observe an AP X C base pair. Both amino protons of AP are seen excluding the rare tautomeric form. Although several alternative structures are possible, it is shown that the second hydrogen bond is formed by protonation of the AP X C base pair and that this is the dominant species under physiological conditions.